ANDEAN COMMUNITY MEMBERS IN THE CHILEAN GOVERNMENT (ARICA, 1880 - 1929) - Díaz Araya, Alberto (Revista de Historia Social y de las Mentalidades, 2011)
Assesses the impact generated in the rural Andes Arica for implementing the administrative structure and bureaucracy in Chile af ter the Pacific War. Through documentary record  makes explicit the participation of indigenous community members in the plot Chilean state  over  a  period  of  political  and  national  identities.
Keywords: Andean Community; Chilean government; Arica and Ta cna